(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Oxalobacter formigenes, as a gram-negative anaerobic bacterium, metabolizes oxalate in the intestine by the enzymes oxalyl-CoA decarboxylase (OXC) and formyl-CoA transferase (FRC). Therefore, not only the presence of the bacterium but also microbial load may affect intestinal absorption and urinary exertion. We evaluated the relationship between Oxalobacter formigenes load and the formation of calcium oxalate urolithiasis using quantitative molecular methods. Methods. By clinical manifestation and stone analysis, we selected the urine and stool specimens of 73 patients with calcium oxalate urolithiasis. First, the gene regions of the two genes FRC and OXC in Oxalobacter formigenes were selected utilizing bioinformatics and specific primers designed for these regions. Following DNA extraction from stool specimens by specific primers of each gene, PCR was carried out and positive samples were sequenced. Then, qPCR was applied to determine the effective load of Oxalobacter. Also, biochemical tests were performed to measure the excretion rate of oxalate in urine specimens. Results. In addition to oxalobacter identification by PCR, the load of bacteria was quantitatively assessed using qPCR by specific primers for both FRC and OXC gene regions. A significant negative relationship had found between the formation of calcium oxalate urolithiasis and the presence of Oxalobacter formigenes in patients with kidney stone disease. The mean excretion of oxalate and citrate in urolithiasis cases were 22.93 and 552.106 mg/24h, respectively. Conclusion. The presence of Oxalobacter formigenes can highly inhibit the generation of calcium oxalate urolithiasis. Furthermore, molecular techniques are more effective than other methods such as culture for the isolation of this bacterium.